Exploring factors affecting peer-led team learning in EFL classes: A case of secondary schools in Ethiopia - Alemayehu, Mastewal Misganaw (Indonesian Journal of Applied Linguistics, 2022)
Peer-led team learning (PLTL) has become common in ESL classrooms across Ethiopia. This study explores factors affecting PLTL in students' verbal participation in English as a Foreign Language (EFL). A descriptive survey was employed as a research method, and mixed approach data collection methods were used. Twenty-four EFL teachers and 114 students of three secondary schools in Ethiopia were taken as the research participants by systematic random sampling. The data collected from questionnaires, interviews, and classroom observation were analyzed qualitatively and quantitatively using a statistical tool in frequency, percentages, ANOVA and multiple regression. The findings indicated that students differ significantly in their level of verbal participation in PLTL groups. Of the twenty-two expected factors, no single factor predicted whether students would participate in PLTL groups. More than one factor was usually working together, or one factor led onto another to affect students' participation. Personality characteristics, motivational factors, and group situation factors were significant to student participation in PLTL. Not every student could get the opportunities to become a group leader, and the groups were static. Since there was an absence of active monitoring, most groups drifted away from tasks and were involved in noisy chat in their mother tongue. Few students in a group dominated others who persevered at group activities. The qualitative findings are consistent with the quantitative ones.